Musical sand characterization - Leach, M.F.; Kilkenny, C. (Canadian Acoustics, 1997)
It is concluded from the experiments that a combination of several agents is responsible for the musical sand phenomenon. In individual cases the presence of too much water, of finely divided material, or of grain angularity has a deleterious effect; but dry, clean and rounded grains by no means always sing and some sands with presumed high moisture content do sing. It is likely that musicality is mediated by a very specific grain-grain surface interaction to which individual grains systems can be tuned in a variety of ways.